SISTEM PENGELOLAAN LABORATORIUM KOMPUTER (Studi Kasus Fakultas Ilmu Komputer Universitas Kuningan) - Dede Irawan; Rio Andriat (NUANSA INFORMATIKA, 2014)
Kuningan University is university which have many faculty. Computer Science Fakulty ( FKOM) is one of them. That  studied in computer science faculty earn divided to become two big group, that is theory and of practice. But role of computer laboratory do not walk by xself, caused some part linking and assisting role of computer laboratory, that is faculty , study program and student giving data about student which have contracted and registration of matakuliah prakticum so that its data can be processed by laboratory as data participant of praktikum. Only in its execution of system management of computer laboratory still use conventional system. With this system is felt still there are  constraints among others : in its result of registration of matakuliah practice have to input repeat by prodi,and than staff require sufficient time, and still there are student which late to registration of matakuliah practice so that data of prodi to laboratory, becoming to lose time. Therefore require to be woke up System Management Of Laboratory Computer. This System use Ianguage of program base on Web, that is PHP and of Mysql. With System management of this computer laboratory can assist related partiess in executing its dutys. Besides System management of this computer laboratory can improve student discipline to execute registration of matakuliah timely, Staff Prodi do not input data  registration. Although that way this management system a long way off from perfection, is therefore expected can provide with schedule facility of praktikum, so that this application can be completed. Keyword : System Management of Computer Laboratory, PHP, MySQL